Probiotics for prevention of atopic diseases in infants: systematic review and meta‐analysis. Issue 11 (13th August 2015) - Zuccotti, G.; Meneghin, F.; Aceti, A.; Barone, G.; Callegari, M. L.; Di Mauro, A.; Fantini, M. P.; Gori, D.; Indrio, F.; Maggio, L.; Morelli, L.; Corvaglia, L.; et al.
Abstract Growing evidence underlines the pivotal role of infant gut colonization in the development of the immune system. The possibility to modify gut colonization through probiotic supplementation in childhood might prevent atopic diseases. The aim of the present systematic review and meta‐analysis was to evaluate the effect of probiotic supplementation during pregnancy and early infancy in preventing atopic diseases. PubMed, Embase and Cochrane Library were searched for randomized controlled trials evaluating the use of probiotics during pregnancy or early infancy for prevention of allergic diseases. Fixed‐effect models were used, and random‐effects models where significant heterogeneity was present. Results were expressed as risk ratio (RR) with 95% confidence interval (CI). Seventeen studies, reporting data from 4755 children (2381 in the probiotic group and 2374 in the control group), were included in the meta‐analysis. Infants treated with probiotics had a significantly lower RR for eczema compared to controls (RR 0.78 [95% CI: 0.69–0.89], P = 0.0003), especially those supplemented with a mixture of probiotics (RR 0.54 [95% CI: 0.43–0.68], P < 0.00001). No significant difference in terms of prevention of asthma (RR 0.99 [95% CI: 0.77–1.27], P = 0.95), wheezing (RR 1.02 [95% CI: 0.89–1.17], P = 0.76) or rhinoconjunctivitis (RR 0.91 [95% CI: 0.67–1.23], P = 0.53) was documented. The results of the present meta‐analysis show that probiotic supplementation prevents infantile eczema, thus suggesting a new potential indication for probiotic use in pregnancy and infancy.